Pertanggungjawaban atas Tindakan Malapraktik Medis Profesi Dokter pada Klinik Kecantikan - Mugiono, Mariana; Indradewi, Astrid Athina; Ginting, Yuni Priskila (Cattleya Darmaya Fortuna, 2025)
Laws are a fundamental component of a state, providing protection and ensuring that every person has the opportunity to receive medical treatment from qualified medical professionals. In the medical field, every action carries the potential for conflict, particularly between medical professionals and patients. When patients experience pain, disability, death, or other adverse outcomes, medical professionals may be accused of malpractice. It is important to recognize that there is always some level of risk involved in any medical procedure, but many patients do not fully understand the difference between malpractice and medical risk, leading to frequent misunderstandings. Malpractice occurs when medical professionals act either intentionally or negligently, which can result in the application of penal laws. In contrast, losses caused by inherent medical risks are not subject to such laws. The actions of doctors and medical professionals are regulated by the Indonesian Criminal Code, Indonesian Civil Code, and the Doctor's Code of Ethics. In conclusion, malpractice involves either intentional wrongdoing or negligence by medical professionals in the provision of medical services, and it is crucial to take steps to prevent such occurrences